2017
DOI: 10.1002/cbic.201700077
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Cellular, Physiological, and Pathological Consequences of Human Loss of N‐Glycolylneuraminic Acid

Abstract: About 2–3 million years ago, Alu‐mediated deletion of a critical exon in the CMAH gene became fixed in the hominin lineage ancestral to humans, possibly through a stepwise process of selection by pathogen targeting of the CMAH product (the sialic acid Neu5Gc), followed by reproductive isolation through female anti‐Neu5Gc antibodies. Loss of CMAH has occurred independently in some other lineages, but is functionally intact in Old World primates, including our closest relatives, the chimpanzee. Although the biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 377 publications
(270 reference statements)
0
67
0
Order By: Relevance
“…The ramifications of this major change in cell surface biochemistry continue to be explored in mouse models of disease [25], and there is evidence for other significant phenotypic effects, including a human-like increase in sensitivity to certain muscular dystrophy pathologies [26][27][28][29]. Although initial muscle studies showed no major differences in the ex vivo force frequency relationship between WT and Cmah null muscle itself [26,27], independent gene expression studies pointed towards alterations in redox biology [30,31], and several transcription factors (cyclic AMP-responsive element-binding protein 1 (CREB1), CCAAT-enhancerbinding protein b (C/EBPb) and CCAAT-enhancer-binding protein a (C/EBPa)) linked to metabolism and inflammation [26].…”
Section: Introductionmentioning
confidence: 99%
“…The ramifications of this major change in cell surface biochemistry continue to be explored in mouse models of disease [25], and there is evidence for other significant phenotypic effects, including a human-like increase in sensitivity to certain muscular dystrophy pathologies [26][27][28][29]. Although initial muscle studies showed no major differences in the ex vivo force frequency relationship between WT and Cmah null muscle itself [26,27], independent gene expression studies pointed towards alterations in redox biology [30,31], and several transcription factors (cyclic AMP-responsive element-binding protein 1 (CREB1), CCAAT-enhancerbinding protein b (C/EBPb) and CCAAT-enhancer-binding protein a (C/EBPa)) linked to metabolism and inflammation [26].…”
Section: Introductionmentioning
confidence: 99%
“…phenotypes (20), are more susceptible to develop glucose intolerance (21), and have hyperreactive macrophages (22), T cells (23), and B cells (24).…”
mentioning
confidence: 99%
“…Potential scenario for the role of Neu5Gc loss and female anti-Neu5Gc immunity in the origin of the genus Homo via interplay of natural and sexual selection acting on cell-surface Sias. There are many known pathogens that recognize and exploit Neu5Gc (blue diamond) as a receptor on host target cells (9). Natural selection by such pathogens may have selected for rare CMAH null alleles that abolish Neu5Gc expression in homozygote individuals (12).…”
Section: Discussionmentioning
confidence: 99%
“…There are many known and possible biological consequences of human Neu5Gc loss, discussed in detail elsewhere (9). Following loss of Neu5Gc biosynthesis, the human immune system also recognizes Neu5Gc-bearing glycans as foreign and antigenic molecules (10,11).…”
mentioning
confidence: 99%